Evaluasi Tingkat Kepuasan Pengunjung Pada Kawasan Pusat Perbelanjaan di Pusat Perbelanjaan Mentaya - Kevin Liandro; Sutan Parasian Silitonga; Murniati Murniati (Jurnal Serambi Engineering, 2023)
Travel attraction, especially in the Mentaya Shopping Center shopping area, is one of the problems that causes congestion. Therefore, it is necessary to solve the transportation problem. The first step is to know the characteristics of the trip attraction and evaluate the level of visitor satisfaction with the current condition of the Mentaya Shopping Center. The research was conducted by distributing questionnaires to 105 respondents at the Mentaya Shopping Center. The analysis used is descriptive analysis to determine the characteristics of the trip attraction and the measurement of the results of the level of visitor satisfaction using a Likert scale. Based on data from filling out questionnaires by 105 respondents, it is known that the average visitor is 21-30 years old, female, most of them work as private workers with the last education of high school (SMA), the average travel time is 20 minutes, the average travel distance is 15 km, the mode used is a motorbike, the highest average income of visitors is Rp. 2,000,000 – Rp. 4,000,000, the origin of most visitors coming from home, the intensity of the visitor's trip for 1 week is 1 time, the purpose of visitors is to buy basic goods. In general, visitors are satisfied with the current state of the Mentaya Shopping Center with a satisfied percentage of 49.5%.